2014
DOI: 10.1080/13803395.2014.963520
|View full text |Cite
|
Sign up to set email alerts
|

Spatial learning in a virtual reality-based task is altered in very preterm children

Abstract: Very preterm births prevent a complete development of the nervous system. The hippocampus is especially vulnerable in this population since the perinatal period is critical for its growth and development. Learning and memory abilities, like spatial memory, depend on the hippocampal integrity. In this study we applied virtual-reality-based tasks to assess spatial memory in a sample of 20 very preterm children of 7 and 8 years of age. Two different conditions of difficulty were used. Very preterm children perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The use of virtual reality to assess spatial memory in humans has shown positive results [8–11]. There are systems created for evaluating spatial memory in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The use of virtual reality to assess spatial memory in humans has shown positive results [8–11]. There are systems created for evaluating spatial memory in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the IQ of children is influenced by the consumption of several nutritional factors [ 22 ]. Low birth weight was also strongly associated with scores on the universal nonverbal intelligence test (UNIT), tests of executive function, and the movement assessment battery for children (MABC) of children in rural eastern Spain [ 23 ]. A study showed that there is a genetic influence from parents on children’s IQ in British and Dutch children [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned previously, spatial orientation is a complex function based on the correct functioning of other sensory and cognitive systems, which leads us to imagine that space navigation may be affected in preterm children. For example, spatial orientation deficits have been observed in preterm, school-aged populations (Cimadevilla, Rold an, Par ıs, Arnedo, & Rold an, 2014). In other clinical populations, such as Williams syndrome (Bernardino, Mouga, Castelo-Branco, & Van Asselen, 2013;Broadbent, Farran, & Tolmie, 2014;Nunes et al, 2013;Vicari, Bellucci, & Carlesimo, 2003), Down syndrome (Lavenex et al, 2015), cerebral palsy (Belmonti, Fiori, Guzzetta, Cioni, & Berthoz, 2015), and fetal alcohol syndrome (Hamilton, Kodituwakku, Sutherland, & Savage, 2003), spatial orientation and visuospatial difficulties have been found as well.…”
Section: Spatial Orientation In Pediatric Neurological Populationsmentioning
confidence: 99%